An orally bioavailable parthenolide analog selectively eradicates acute myelogenous leukemia stem and progenitor cells - Guzman, Monica L. (American Society of Hematology, 2007)
Leukemia stem cells (LSCs) are thought to play a central role in the pathogenesis of acute leukemia and likely contribute to both disease initiation and relapse. Therefore, identification of agents that target LSCs is an important consideration for the development of new therapies. To this end, we have previously demonstrated that the naturally occurring compound parthenolide (PTL) can induce death of human LSCs in vitro while sparing normal hematopoietic cells. However, PTL has relatively poor pharmacologic properties that limit its potential clinical use. Consequently, we generated a family of PTL analogs designed to improve solubility and bioavailability. These studies identified an analog, dimethylamino-parthenolide (DMAPT), which induces rapid death of primary human LSCs from both myeloid and lymphoid leukemias, and is also highly cytotoxic to bulk leukemic cell populations. Molecular studies indicate the prevalent activities of DMAPT include induction of oxidative stress responses, inhibition of NF-κB, and activation of p53. The compound has approximately 70% oral bioavailability, and pharmacologic studies using both mouse xenograft models and spontaneous acute canine leukemias demonstrate in vivo bioactivity as determined by functional assays and multiple biomarkers. Therefore, based on the collective preclinical data, we propose that the novel compound DMAPT has the potential to target human LSCs in vivo.